Rapid Detection of Heavy Metals with the Response of Carotenoids in Daucus Carota - Wong, Ling Shing; Choong, Chieh Wean (IJESD, 2014)
In this paper, a rapid detection method for heavy metals (Cu, Pb and Zn) is reported. The method was based on the response of natural cell-bounded carotenoids in Daucus carota to short term exposure of heavy metals. The cells were cultured for 90 days in dark. The presence of carotenoids in cells was confirmed spectrometrically with optical density (OD) measured at λ= 450 nm. The responses of the cells to 0.01, 0.10, and 1.00 ppm of heavy metals were confirmed by the increase of OD after the short term exposure, with the lowest detection were recorded at 0.01, 0.10, and 0.01 ppm respectively. The OD increase might be a result of the synthesis of carotenoids, which was probably triggered by the increase of oxidative stress. With an average optimum response time of 40 minutes, the cell could be potentially utilized in biosensor.